2014
DOI: 10.1111/1755-0998.12288
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and sensitive identification and quantification of airborne pollen using next‐generation DNA sequencing

Abstract: Pollen monitoring is an important and widely used tool in allergy research and creation of awareness in pollen-allergic patients. Current pollen monitoring methods are microscope-based, labour intensive and cannot identify pollen to the genus level in some relevant allergenic plant groups. Therefore, a more efficient, cost-effective and sensitive method is needed. Here, we present a method for identification and quantification of airborne pollen using DNA sequencing. Pollen is collected from ambient air using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
257
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(272 citation statements)
references
References 51 publications
10
257
1
4
Order By: Relevance
“…In addition to these features, eDNA studies need to consider the anatomical location and physiological shedding of different genomes in target taxa. For example, the quantity of chloroplasts in angiosperm pollen varies across species, making the choice of plastid or nuclear genomes important for studies of plant eDNA in air, sediment, or pollinator forage (Bennett and Parducci 2006;Kraaijeveld et al 2015;Richardson et al 2015). Metazoan eDNA studies have tended to use mitogenome regions because of the higher number of mitochondrial versus nuclear genomes per cell (Rees et al 2015); however, eukaryotic ribosomal DNA copy number per nuclear genome can reach 19,300 in animals and 26,048 in plants (Prokopowich et al 2003)-numbers which are comparable to the largest numbers of mitogenomes per cell (e.g., 22,000; Caldwell et al 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these features, eDNA studies need to consider the anatomical location and physiological shedding of different genomes in target taxa. For example, the quantity of chloroplasts in angiosperm pollen varies across species, making the choice of plastid or nuclear genomes important for studies of plant eDNA in air, sediment, or pollinator forage (Bennett and Parducci 2006;Kraaijeveld et al 2015;Richardson et al 2015). Metazoan eDNA studies have tended to use mitogenome regions because of the higher number of mitochondrial versus nuclear genomes per cell (Rees et al 2015); however, eukaryotic ribosomal DNA copy number per nuclear genome can reach 19,300 in animals and 26,048 in plants (Prokopowich et al 2003)-numbers which are comparable to the largest numbers of mitogenomes per cell (e.g., 22,000; Caldwell et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Distinguishing between eDNA signals of organism abundance and organism proximity (in both space and time) represents an emerging challenge for research along this frontier. Water and air can rapidly transport eDNA across long distances Kraaijeveld et al 2015), and eDNA decays exponentially in the environment (Barnes et al 2014). Thus, models that include eDNA production, transport, and decay may improve the ability to infer organism abundance from eDNA quantity.…”
Section: Estimation Of Organism Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…Following similar observations, suggestions that plastid DNA (ptDNA) was absent from the pollen (e.g., Willerslev et al 2003) may have discouraged early development of pollen DNA barcoding methods. Several studies have now shown proof-of-concept for amplification of ptDNA from pollen (Galimberti et al 2014;Hawkins et al 2015;Kraaijeveld et al 2015;Richardson et al 2015a), so this is no longer considered an issue.…”
Section: Background and Potential Of Pollen Dna Barcodingmentioning
confidence: 99%
“…These methods 782 offer the potential to study plant-pollinator networks as DNA from bulk samples contains not 783 only pollinator DNA, but also any associated organic material such as pollen, parasites and 784 pathogens ( Figure 7). Using a read-matching approach, matching DNA from pollen would 785 allow the practitioner to populate plant-pollinator networks in a more direct fashion than 786 studies using visitation as a proxy (King et al, 2013), and more rapidly, reliably and to a 787 higher resolution than microscopy methods (Kraaijeveld et al, 2015). Presently plant 788 identification via molecular approaches still rely on several short chloroplast barcodes but 789 whole chloroplast genome sequencing is expanding rapidly, which will overcome the 790 problem of low chloroplast abundance in the pollen, currently addressed with sequencing of 791 the nuclear ITS region (Bohmann et al, 2014;Keller et al, 2015;Richardson et al, 2015;792 Sickel et al, 2015).…”
mentioning
confidence: 99%